1998
DOI: 10.1111/j.1365-2672.1998.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships amongPseudomonas stutzeristrains based on molecular typing methods

Abstract: A . B EN N AS AR , C. GU A SP , M . TE SA R AN D J . LA LU C AT . 1998. Detailed characterization of the genetic variability among strains belonging to Pseudomonas stutzeri was achieved using different rapid molecular typing methods based on polymerase chain reaction (PCR), Southern blot and Western blot. Consensus motifs complementary to fragments of repetitive elements dispersed throughout the genomes of bacteria were used as primers and allowed differentiation at subspecies levels. Further and simple differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
4
20
0
Order By: Relevance
“…The genomovar structure of P. stutzeri is consistent with the finding of seven genotypic groups in a genomic fingerprint analysis (Sikorski et al, 1999). Variable grouping of various strains in cluster analyses of genomic fingerprints and macrorestriction patterns indicated that chromosomal rearrangements, presumably also a result of horizontal gene transfer, have occurred and contributed to the extremely high genotypic diversity within this species (Bennasar et al, 1998 ;Ginard et al, 1997 ;Rainey et al, 1994 ;Sikorski et al, 1999).…”
Section: Introductionsupporting
confidence: 59%
“…The genomovar structure of P. stutzeri is consistent with the finding of seven genotypic groups in a genomic fingerprint analysis (Sikorski et al, 1999). Variable grouping of various strains in cluster analyses of genomic fingerprints and macrorestriction patterns indicated that chromosomal rearrangements, presumably also a result of horizontal gene transfer, have occurred and contributed to the extremely high genotypic diversity within this species (Bennasar et al, 1998 ;Ginard et al, 1997 ;Rainey et al, 1994 ;Sikorski et al, 1999).…”
Section: Introductionsupporting
confidence: 59%
“…Similar genomic relationships have been revealed by PCR amplification of several genes (16S rRNA, internal transcribed spacer region 1 [ITS1], ITS2, and rpoB) and by analyzing the RFLPs generated by several restriction enzymes (25,133,325). These methods have confirmed the high genetic diversity of the species, the consistency of genomic groups (genomovars), and the usefulness of the patterns generated for strain identification.…”
Section: Genotypingmentioning
confidence: 49%
“…However, a similar procedure, based on Western blotting and immunological fingerprinting of whole-cell proteins using the polyclonal antibody Ab160, raised against Pseudomonas fluorescens MT5-called Westprinting (360)-produced a typical protein profile for each strain. Computer-assisted comparisons revealed a distribution in groups that agreed with the strains' genomovar distribution at different similarity levels (25).…”
Section: Chemical Characterization and Chemotaxonomymentioning
confidence: 92%
See 1 more Smart Citation
“…and biochemical method and then they were Established conventional methods to detect and confirmed by invA specific PCR methods. identify Salmonella are time consuming and include Materials and Methods selective enrichment and plating followed by biochemical tests (Bennasar et al, 2000;Burtscher et al, Samples from broiler carcasses and culture 1999; Chiu and Jonathan, 1996). Several techniques methods: Sixty samples of broilers were collected have been developed for the improvement in the from slaughter houses of Namakkal.…”
Section: Introductionmentioning
confidence: 99%